2009
DOI: 10.1002/ejlt.200800169
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dehydroepiandrosterone on lipogenic gene mRNA expression in cultured primary chicken hepatocytes

Abstract: The effects of dehydroepiandrosterone (DHEA) on lipogenic gene mRNA expression were examined using cultured primary chicken hepatocytes. Cell samples were equilibrated to culture conditions for 24 h and then exposed to DHEA (1, 10 and 100 mM) dissolved in DMSO. The expression of sterol regulatory element-binding protein-1 (SREBP-1) mRNA in cultured primary hepatocytes did not vary with time, except for a significant decrease in gene expression when cells were treated with 10 or 100 mM DHEA for either 1 or 2 h.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…No significant change was detected in mitochondria number and their configuration in primary Leydig cells following DHEA treatment. However, previous studies have demonstrated that DHEA affects mitochondrial number and configuration in chicken hepatocytes ( 20 ) and the liver of male rats ( 39 ). DHEA also increases fatty acid β-oxidation and enhances mitochondrial respiration, which may be the cause of the decrease in mitochondria number in the rat or chicken liver cells ( 20 , 39 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…No significant change was detected in mitochondria number and their configuration in primary Leydig cells following DHEA treatment. However, previous studies have demonstrated that DHEA affects mitochondrial number and configuration in chicken hepatocytes ( 20 ) and the liver of male rats ( 39 ). DHEA also increases fatty acid β-oxidation and enhances mitochondrial respiration, which may be the cause of the decrease in mitochondria number in the rat or chicken liver cells ( 20 , 39 ).…”
Section: Discussionmentioning
confidence: 93%
“…The method used in the present study was modified from the method described by Tang et al ( 20 ). Briefly, primary rat Leydig cells were cultured in 6-well plates (1×10 6 cells/well) and treated with 1 μ M, 50 μ M and 100 μ M DHEA.…”
Section: Methodsmentioning
confidence: 99%